2018
DOI: 10.1111/iej.13029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, predictive factors and clinical course of persistent pain associated with teeth displaying periapical healing following nonsurgical root canal treatment: a prospective study

Abstract: Aims To investigate the prevalence, pain catastrophizing and other predictive factors and clinical course of persistent pain/discomfort associated with teeth displaying periapical healing following nonsurgical root canal treatment (NSRCT). Methodology One hundred and ninety‐eight patients (264 teeth) who had NSRCT were reviewed at 5–14 months, postoperatively. Teeth with persistent post‐treatment pain or discomfort, plus evidence of periapical healing were further monitored 0.5, 4 and 10 years later. Pain Cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 30 publications
(85 reference statements)
2
27
0
Order By: Relevance
“…There is therefore a risk that the results overestimate the proportion of patients in the adult population who experience symptoms from their root filled tooth. However, the findings agree with earlier studies reporting on frequency of post-treatment pain from root filled teeth (Polycarpou et al 2005, Nixdorf et al 2010a, Vena et al 2014, Philpott et al 2018.…”
Section: Participationsupporting
confidence: 92%
See 3 more Smart Citations
“…There is therefore a risk that the results overestimate the proportion of patients in the adult population who experience symptoms from their root filled tooth. However, the findings agree with earlier studies reporting on frequency of post-treatment pain from root filled teeth (Polycarpou et al 2005, Nixdorf et al 2010a, Vena et al 2014, Philpott et al 2018.…”
Section: Participationsupporting
confidence: 92%
“…, Philpott et al . ). However, there are no published studies specifically screening for overall frequency of pain associated with root filled teeth in a general population.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This challenge can be overcome with the use of the bite force transducer as an objective diagnostic tool. Notably, several studies have identified predictors for postoperative endodontic pain, including intensity and duration of the preoperative pain and patient sex and age [11][12][13][14] . Although these are strong predictors for postoperative pain, and possibly its transition into chronic odontogenic pain, far little is known about their association with the magnitude of MA, a chief complaint in persistent endodontic pain 11 .…”
Section: Significancementioning
confidence: 99%